Recent Developments and Potential for Clinical Use of Casein as a Drug Carrier - Semwal, Ravindra; Joshi, Sunil K.; Semwal, Ruchi Badoni; Semwal, Deepak Kumar (Current Drug Delivery, 2023)
Background: The development of drug delivery carriers is the key area of research in the field of novel drug delivery systems. To date, a long list of carriers has been identified for this purpose but the deliveries of poorly water-soluble active substances are still facing challenges and hence, such substances are pharmacologically unsafe and economically incompetent. Objective: This article aims to review the applications of casein as a drug carrier and its potential for clinical use. Methods: The relevant literature on the casein protein was collected from authentic online scientific databases like PubMed, Scopus and Google Scholar using different keywords including “casein”, “drug delivery system”, “drug carrier” and “bioavailability”. The articles and books accessed online have been thoroughly reviewed and the most relevant reports on casein as a drug carrier have only been included in the present study. Results: Casein is a milk protein that has many structural and physicochemical properties which facilitate its functionality in delivery systems. Moreover, its amphiphilic nature makes it the most suitable carrier for both hydrophobic and hydrophilic drugs without showing any toxic effects. The carriers obtained from natural sources are trustworthy over synthetic carriers and in the demand of the market due to their easy availability, low-cost factor, bio-friendly and nontoxic nature. Conclusion: Casein was found to be an effective natural drug carrier in various delivery systems due to its unique applications in improving the bioavailability and efficacy of a drug.
Keywords: nanoparticles